Targeting post-stroke neuroinflammation with Salvianolic acid A: molecular mechanisms and preclinical evidence - Yang, Hongchun; Ibrahim, Muhammad Mustapha; Zhang, Siyu; Sun, Yao; Chang, Junlei; Qi, Hui; Yang, Shilun (Frontiers in Immunology, 2024)
Salvianolic acid A (SalA), a bioactive compound extracted from Salvia miltiorrhiza, has garnered considerable interest for its potential in ameliorating the post-stroke neuroinflammation. This review delineates the possible molecular underpinnings of anti-inflammatory and neuroprotective roles of SalA, offering a comprehensive analysis of its therapeutic efficacy in preclinical studies of ischemic stroke. We explore the intricate interplay between post-stroke neuroinflammation and the modulatory effects of SalA on pro-inflammatory cytokines, inflammatory signaling pathways, the peripheral immune cell infiltration through blood-brain barrier disruption, and endothelial cell function.The pharmacokinetic profiles of SalA in the context of stroke, characterized by enhanced cerebral penetration post-ischemia, makes it particularly suitable as a therapeutic agent. Preliminary clinical findings have demonstrated that salvianolic acids (SA) has a positive impact on cerebral perfusion and neurological deficits in stroke patients, warranting further investigation. This review emphasizes SalA as a potential anti-inflammatory agent for the advancement of innovative therapeutic approaches in the treatment of ischemic stroke.